The effect of laser radiation on DNA damage and repair - Dhiaa Ridha, Farah; Zaki Salih, Anmar; Abdul–Majeed, Ban A. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: The effect of Helium Neon laser (He-Ne 632.8 nm) was reported to protect cells from damage. We studied lymphocyte cells pre irradiated with (UVC 260 nm) to induce DNA damage. Investigations were carried using gel electrophoresis and test for cell viability. It has also been reported that effect depends on incubation period after damage. The extent of damage to the cells depends on the period of irradiation with UVC also on its intensity. Objective: In this work we studied the effect of UVC on DNA damage and cell survival Also study of the effect of He-Ne laser on cell survival after all being pre irradiated with UVC light and its protective effect on DNA post UV damage. Method: This study was conducted in pathology department post graduate laboratory - College of medicine-Baghdad University. The total number of samples was (147). Blood samples were collected from healthy donors came to the blood bank, the amount of blood drown varies from 5ml to 7ml in heparin tubes .The work was carried out during the period between November 2010 to August 2011. In this experiments examination of samples was carried out to test the radiation effect on cell viability by using trypan blue dye, the experiments were preformed after 1, 24 and 72 hours post UVC irradiation to test the repair development. In other experiments Gel electrophoresis were carried out on samples to study the effect of radiation on the DNA fragmentation. Result: Results reveal a reduced DNA fragmentation appeared on gel electrophoresis experiments as the smear length is reduced significantly for both UV10 and UV20 , other results for cell viability tests revelled that He-Ne can increase survival of cells pre irradiated with UVC irradiation giving (66%, 57%, 70%( improvement in UV exposure for10 min and (59%,56%,59%) improvement for UV exposure for 20 min respectively . Conclusion: The effect of the laser in the improvement of cell survival may be attributed to the induction of endogenous radioprotectore and probably enzymes induced by laser irradiation which may be either reduce the free radical by scavenging effect or by improved cell repair, we may conclude that He-Ne laser can protect cells from radiation damage